برنامج تدريبي لتحسين بعض العمليات العقلية الأساسية لأطفال ما قبل المدرسة المعاقين عقليا القابلين للتعلم - قناوي، هدى محمد; علي، هند مسعد إبراهيم; رضوان، نهي عبدالحميد محمود Radwan, Noha Abdulhamid Mahmoud (جامعة بورسعيد - كلية رياض الأطفال, 2019)
يهدف البحث الحالي إلى تحسين بعض العمليات العقلية الأساسية " الانتباه، الإدراك، الذاكرة، لأطفال ما قبل المدرسة المعاقين عقليا القابلين للتعلم من خلال إعداد برنامج تدريبي. وقد تكونت عينة البحث الحالي من (٢٥) طفلا وطفلة من الأطفال المعاقين عقليا ذي التصميم التجريبي المجموعة الواحدة من الأطفال المعاقين عقليا القابلين للتعلم حيث يتراوح العمر العقلي لهؤلاء الأطفال ما بين (55 -٧٠)، والعمر الزمني ما بين (١٠ - ١٤) سنة وتم تطبيق البرنامج بمدرسة التربية الفكرية بمحافظة بورسعيد، وأجري البحث في الفصل الدراسي الأول للعام الدراسي ٢٠١٨/ ٢٠١٩ م، واستخدمت الباحثة مقياس اختبار الذكاء ستانفورد بينيه الصورة الخامسة ( إعداد / محمود أبو النيل، ٢٠٠٩)، استمارة المستوى الاقتصادي والاجتماعي والثقافي للأسرة ( إعداد كمال دسوقي، محمد بيومي خليل،٢٠٠٠) وقائمة العمليات العقلية الأساسية، مقياس العمليات العقلية الأساسية للأطفال المعاقين عقليا القابلين للتعلم، وبرنامج تدريبي لتحسين بعض العمليات العقلية الأساسية لأطفال ما قبل المدرسة المعاقين عقليا القابلين للتعلم (إعداد/ الباحثة). وأشارت نتائج البحث الحالي إلى وجود فرق دال إحصائيا بين متوسطي درجات أطفال المجموعة التجريبية على مقياس العمليات العقلية الأساسية في التطبيقين القبلي والبعدي لصالح التطبيق البعدي، بالإضافة إلى عدم وجود فرق دال إحصائيا بين متوسطي درجات أطفال المجموعة التجريبية على مقياس العمليات العقلية الأساسية في التطبيقين البعدي والتتبعي.
The current research aims to improve some basic mental processes "attention, cognition, memory" for mentally handicapped children who can learn through the preparation of a training program. The current research sample consisted of (25) children with mental disabilities with experimental design, a single group of mentally handicapped children who can learn, ranging in age from 55-70, age between (10-14) years and the program was implemented at the School of Intellectual Education in Port Said Governorate, and the research was conducted in the first semester of the academic year 2018 /2019, and the researcher used the iq test scale (prepared / Stanford Binet), the child's preliminary data form from the children's record of the school of intellectual education in Port Said governorate and the list of mental processes, the scale of mind operations, For children with learning mental disabilities, and a training program to improve some basic mental processes for pre-school children with learning mental disabilities (preparation/researcher). The results of the current research indicated that there is a statistical lyceum between the average grades of the children of the experimental group on the scale of basic mental processes in the tribal and dimensional applications in favor of the dimensional application, in addition to the absence of a statistical d difference between the average grades of the experimental group children on the scale of basic mental processes in the dimensional and tracking applications.
Keywords: العمليات العقلية -- مرحلة رياض الاطفال -- الاعاقة الذهنية